Antinociceptive, anti-inflammatory, and antipyretic properties of an aqueous extract of Dicranopteris linearis leaves in experimental animal models - Zakaria, Zainul Amiruddin; Abdul Ghani, Zuleen Delina Fasya; Raden Mohd Nor, Raden Nur Suraya; Gopalan, Hanan Kumar; Sulaiman, Mohd Roslan; Mat Jais, Abdul Manan; Somchit, Muhammad Nazrul; Abdul Kadir, Arifah; Ripin, Johari (Springer, 2008)
This study was performed out to establish the antinociceptive, anti-inflammatory, and antipyretic properties of an aqueous extract of Dicranopteris linearis leaves in experimental animals. The antinociceptive activity was measured using the abdominal constriction, hot plate, and formalin tests. The anti-inflammatory and antipyretic activities were measured using the carrageenan-induced paw edema and brewer's yeast-induced pyrexia tests, respectively. The extract, obtained after 72 h soaking of the air-dried leaves in distilled water and then prepared in the doses of 13.2, 66.0, 132.0, and 660.0 mg/kg, was administered subcutaneously 30 min before subjecting the animals to the assays mentioned above. Generally, the extract, at all doses used, was found to have significant (P < 0.05) concentration-independent antinociceptive, anti-inflammatory, and anti-pyretic activity. In conclusion, the aqueous extract of D. linearis has antinociceptive, anti-inflammatory, and antipyretic activity, supporting previous claims of its traditional use by the Malays to treat various ailments, particularly fever.